Social pedagogy and sociology of education – in a circle of mutual inspirations - Segiet , Katarzyna (Studia Edukacyjne, 2019)
The state and future of scientific disciplines is largely determined by their background, numerous important events, discoveries, achievements, but above all, eminent experts, people of science. Thanks to these people, it was possible to conduct many analyses and research programs, which were reflected in multiple scientific studies. In the case of Polish social pedagogy, Helena Radlińska, Aleksander Kamiński and Ryszard Wroczyński have undoubtedly become such persons. On the other hand, Polish sociology of education should be strongly associated, among others, with Florian Znaniecki, Józef Chałasiński and Stanisław Kowalski. In this article, I do not describe all the issues that are the focus of both subdisciplines. However, I would like to underline a few issues that I will present synthetically and which are personally important and interesting from the point of view of a social educator, namely: What are the sources of the emergence of social pedagogy as a scientific discipline and what associates it with the sociology of education; What priorities are imposed on social pedagogy and sociology of upbringing by the transformation of modern civilization and how are new social problems shaped in this context; finally how educational sociology has been an aid to social pedagogy and vice versa.